Relationship between firm valuation, business practices and earnings management: a meta-analysis / Ajay Ranjitha and R Madhumathi. - Ranjitha, Ajay; Madhumathi, R (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
The objective of this paper is to meta-analyze the result of relevant literature capturing the relationship measured in terms of correlation coefficient between valuation and earnings management; business practices (corporate governance) and earnings management; select business practices (financial constraints, credit quality, diversification strategy, product market compeition) and earnings management. We examined 30 empirical studies for the period 2006 to 2015 reflecting 53 correlations among the variables. The result indicates that corporate governance measured using governance index, audit opinion, institutional ownership, family ownership, promoter ownership, dual share, board size, CEO duality and board index have a significant negative relationship with earnings management. This signifies that an effective governance mechanism reduces the extent of earnings management in the firm. The moderator analysis confirmed that the result is similar across different measures of earnings management. In addition, select business practices (product market competition, financial constraints, credit ratings, diversification strategy) show a significant negative relationship with earnings management.